THE MEDIA PRODUCTION OF “THE POOR OF THE CITY”: THE CASE OF THE RAMONA TELEVISION SERIES - Santa Cruz, Eduardo (Revista de Historia Social y de las Mentalidades, 2021)
This article provides a close reading of the visual portrayals about “the impoverished inhabitants of the city” as a social movement. It does so by analyzing Ramona, a fiction television series broadcast by the Chilean public television in 2017 and 2018. The story is set in 1967 and it depicts a complex overview fueling what we call a visual common sense and media social memory about both the historical period and the phenomenon Ramona illustrates. The media production about “the impoverished inhabitants of the city” is more than one hundred years old and it has been represented by a plurality of languages, genres, styles, and cultural artifacts. Books, cartoons, films, or radio programming have promoted readings of popular characters, lives, and processes that have been key to the Chilean history and also a part of a cultural common sense. Ramona follows those previous paths at the same time it opens new media and interpretative clues, too.